2016
DOI: 10.1371/journal.pone.0165200
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized Phospholipid OxPAPC Activates TRPA1 and Contributes to Chronic Inflammatory Pain in Mice

Abstract: Oxidation products of the naturally occurring phospholipid 1-palmitoyl-2-arachidonoyl-sn-glycerol-3-phosphatidylcholine (PAPC), which are known as OxPAPC, accumulate in atherosclerotic lesions and at other sites of inflammation in conditions such as septic inflammation and acute lung injury to exert pro- or anti-inflammatory effects. It is currently unknown whether OxPAPC also contributes to inflammatory pain and peripheral neuronal excitability in these conditions. Here, we observed that OxPAPC dose-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 51 publications
(56 reference statements)
1
48
0
Order By: Relevance
“…These conditions are often associated with an increased endogenous aldehyde load. Endogenous unsaturated aldehydes such as 4-hydroxynonenal (4-HNE), often contained within oxidized phospholipids and associated with asthma, and methylglyoxal, associated with diabetes, were identified as TRPA1 agonists, suggesting that chronic activity of TRPA1 may contribute to the disease etiology of these conditions (Trevisani et al, 2007; Ohkawara et al, 2012; Liu et al, 2016). …”
Section: Trpa1 a Receptor For Acrolein In Sensory Neuronsmentioning
confidence: 99%
“…These conditions are often associated with an increased endogenous aldehyde load. Endogenous unsaturated aldehydes such as 4-hydroxynonenal (4-HNE), often contained within oxidized phospholipids and associated with asthma, and methylglyoxal, associated with diabetes, were identified as TRPA1 agonists, suggesting that chronic activity of TRPA1 may contribute to the disease etiology of these conditions (Trevisani et al, 2007; Ohkawara et al, 2012; Liu et al, 2016). …”
Section: Trpa1 a Receptor For Acrolein In Sensory Neuronsmentioning
confidence: 99%
“…Recently, we and others have shown that OxPL including oxidized 1‐palmitoyl‐2‐arachidonoyl‐sn‐glycero‐3‐phosphocholine (OxPAPC) activate heterologous and native TRPA1 as well as TRPV1 channels in vitro . Once locally injected, these lipids elicit thermal and mechanical hypersensitivity as well as acute nociception in vivo (Patwardhan et al ., ; Liu et al ., ; Oehler et al ., ). Furthermore, we showed that OxPAPC‐mediated activation of TRPA1 channels in vitro , as well as thermal and mechanical hypersensitivity induced by OxPAPC in vivo are blocked by a function‐blocking autoantibody against oxidized phosphatidylcholine (OxPC), the E06 monoclonal antibody (Oehler et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Nrf2 in macrophages was shown to exert direct anti-inflammatory effects[83] and an anti-inflammatory, reparative function in the brain was ascribed to Mox macrophages detected in microglia after stimulation of nicotinic receptors[84]. Of note, a recent report demonstrated regulation of chronic inflammatory pain by OxPAPC in neurons via activation of TRPA1 channels[85]. …”
Section: Oxpl and Macrophages: Identification Of Moxmentioning
confidence: 99%